PENGARUH TINGKAT KEBISINGAN TERHADAP TINGKAT KESEHATAN PENDENGARAN KARYAWAN DI PT. MITRA BARITO DESA PARING LAHUNG KECAMATAN MONTALLAT KABUPATEN BARITO UTARA KALIMANTAN TENGAH - Sri Rahmawati; Idiannoor Mahyudin; Rukmini Rukmini; Danang Biyatmoko (EnviroScienteae, 2026)
Noise is one of the physical hazards that can potentially cause hearing health problems for employees, especially in the mining sector. The operational activities of PT. Mitra Barito generate noise from generators, crushers, conveyor machines, and heavy equipment traffic. This study aims to identify the sources and types of noise, measure noise levels in the work environment, analyze the impact of noise on employees' hearing health, and evaluate the noise control measures implemented by the company. The research was conducted from August to December 2025 in the workshop area, jetty, office, and ROM 17 of PT. Mitra Barito, North Barito Regency, Central Kalimantan. The research method used was action research with a descriptive qualitative and quantitative approach. Data were collected through noise measurements using a sound level meter, field observations, interviews, and questionnaires administered to 41 respondents who were selected through purposive sampling. Based on the results of noise level measurements in the workshop (101.3 dB), jetty (88.1 dB), office (unit traffic) (85.1 dB), and ROM 17 (92.1 dB), the levels exceed the NAB (85 dB). Therefore, employees working in these areas are required to use PPE in the form of Earplugs or Ear Muffs to prevent hearing impairment.